Aparādha aura daṇḍa : aparādhake kāraṇa aura nivāraṇakā manovaijñānīka vivecana - Gupta, Parmeshwari Lal, 1914- (SAMP early 20th-century Indian books project ;, 1943)
On crime and punishment in India.